DEVELOPMENT OF MONITORING SYSTEM FRAMEWORK FOR THE PRODUCT DOCUMENTS-MAKING PROCESS: CASE STUDY OF RAILWAY MANUFACTURING INDUSTRY - Sahid Putra, Yunandaru
The purpose of this research is to apply the Industry 4.0 concept in the form of developing an activity monitoring system in the Engineering Department of the railroad industry. The railroad manufacturing industry is an industry characterized by Engineered to Order (ETO) and One of a Kind Production (OKP) production which has a high level of complexity, and changes occur quickly and dynamically. ETO is a new product to be made based on customer requests. While OKP is that each product produced will always be unique to each project. One of the issues that will be raised is overcoming delays in completing product documents against the prearranged design schedule. Product documents are initial documents made after receiving technical specifications from customers which contain technical description documents, technical calculations, technical simulations and concept drawings. The product document will be used as a reference for further processes such as making design drawings, purchasing contracts, and making work instruction documents. If there is a delay in this document, it will cause the next process to experience potential delays. So to prevent this, the product document creation process is monitored by modeling it in the virtual world. This model will receive feedback from changes that occur in the field. So that the data stored in the model can be retrieved and processed to produce useful information to monitor the progress of the ongoing process. One of them is information about the progress of document creation which can be used to find out what documents are currently being worked on and have been completed. Other information is related to being able to trace documents that contain identity and when the documents were completed. As well as knowing the performance information of employees who make documents so that employee performance evaluations can be carried out objectively and through data recorded by the system. In the end management can make decisions more quickly based on the same and transparent information sources.